Oscar's lion : 'Beautiful, adventurous, powerful' - Baron, Adam; Davies, Benji (London : Harper Collins Children's Book, 2023)
Oscar is a little terrified to find that a lion is going to be looking after him for the weekend. But when the lion lets him eat as many biscuits as he wants, and reads him his favorite story ten times, Oscar realizes he might be on to something good. Soon, Oscar discovers that the lion can change into different animals and the pair find themselves having all kinds of adventures! But before the lion has to go, might he have one more amazing transformation up his sleeve?
Keywords: Animal -- Fiction